2023
DOI: 10.1371/journal.pone.0283233
|View full text |Cite
|
Sign up to set email alerts
|

UK alcohol consumption during the COVID-19 pandemic: The role of drinking motives, employment and subjective mental health

Abstract: Background Previous investigations suggest that the COVID-19 pandemic effects on alcohol consumption were heterogenous and may vary as a function of structural and psychological factors. Research examining mediating or moderating factors implicated in pandemic-occasioned changes in drinking have also tended to use single-study cross-sectional designs and convenience samples. Aims: First, to explore structural (changed employment or unemployment) and psychological (subjective mental health and drinking motives)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…The results of a large study that evaluated alcohol use during the COVID-19 pandemic in the United Kingdom suggested that being older is associated with increased alcohol consumption [49]. In our study, the COVID-19-positive group had more alcohol users, though this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 87%
“…The results of a large study that evaluated alcohol use during the COVID-19 pandemic in the United Kingdom suggested that being older is associated with increased alcohol consumption [49]. In our study, the COVID-19-positive group had more alcohol users, though this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 87%
“…It may be surprising that deaths following alcohol use did not change following the first lockdown, as it is well documented that alcohol use increased for many people (77)(78)(79)(80). However, NPSAD reporting criteria is dependent upon psychoactive drug use, so any alcohol-related deaths are actually combined drug-and alcohol-related.…”
Section: Fatal Opioid Overdose Characteristics Changed Despite No Cha...mentioning
confidence: 99%